A highly sensitive fluorescent probe for hydrazine detection: synthesis, characterisation and application in living cells. Issue 8 (21st June 2021) - Ye, Hui; Chen, Li; Wang, Xinxian; Lu, Dingqiang
ABSTRACT: A new fluorescent probe HSL-AI derived from imidazo [1, 5- a ]pyridine was synthesised for the detection of hydrazine (N2 H4 ) based on excited-state intramolecular proton transfer (ESIPT). HSL-AI was designed using acetyl group as the recognition site and exhibited high selectivity towards N2 H4 with a low limit of detection (2.56 ppb). Moreover, HSL-AI was successfully applied to detect N2 H4 in living cells.